2022
DOI: 10.1101/2022.10.28.514222
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Three-dimensional imaging and single-cell transcriptomics of the human kidney implicate perturbation of lymphatics in alloimmunity

Abstract: Studies of the structural and molecular features of the lymphatic vasculature, which clears fluid, macromolecules and leukocytes from the tissue microenvironment, have largely relied on animal models, with limited information in human organs beyond traditional immunohistochemical assessment. Here, we use three-dimensional imaging and single-cell RNA-sequencing to study lymphatics in the human kidney. We found a hierarchical arrangement of lymphatic vessels within human kidneys, initiating along specialised nep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 118 publications
(195 reference statements)
0
8
0
Order By: Relevance
“…DEGs between healthy and ADPKD kidneys for each blood EC subset were visualised using the EnhancedVolcano package. Gene ontology (GO) analysis was performed using the PANTHER webtool for gene classification (42) as previously described (33). Marker genes were selected based on the following criteria: i) an adjusted p value > 0.05 from a Wilcoxon rank sum test; ii) a log 2 FC value greater than 1; iii) within the top ten DEGs when lists of genes were ordered by log 2 FC (iv) non-secreted proteins to be identifiable by subsequent immunofluorescence experiments; (v) specificity of the transcript for vascular ECs by visual inspection of feature plots and (vi) consistent expression across the same specialised EC subtype across three or more of the datasets used to generate the scRNA-seq atlas, examined using a dot plot.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…DEGs between healthy and ADPKD kidneys for each blood EC subset were visualised using the EnhancedVolcano package. Gene ontology (GO) analysis was performed using the PANTHER webtool for gene classification (42) as previously described (33). Marker genes were selected based on the following criteria: i) an adjusted p value > 0.05 from a Wilcoxon rank sum test; ii) a log 2 FC value greater than 1; iii) within the top ten DEGs when lists of genes were ordered by log 2 FC (iv) non-secreted proteins to be identifiable by subsequent immunofluorescence experiments; (v) specificity of the transcript for vascular ECs by visual inspection of feature plots and (vi) consistent expression across the same specialised EC subtype across three or more of the datasets used to generate the scRNA-seq atlas, examined using a dot plot.…”
Section: Methodsmentioning
confidence: 99%
“…We generated a transcriptomic atlas of the renal microvasculature using previously published single-cell RNA sequencing (scRNA-seq) data of healthy and diseased human kidneys (33). Healthy samples constituted tissues from donor kidneys which were not suitable for transplantation, non-rejection biopsies from kidney transplants or non-tumorous regions from tumour nephrectomies.…”
Section: Sample Acquisition and Pre-processingmentioning
confidence: 99%
See 2 more Smart Citations
“…Bo ¨hner et al [45] reported that renal denervation exacerbates LPS and antibody-induced acute kidney Injury and inflammation, but protects from pyelonephritis. Tissue clearing has provided more detailed insights into the development and structure of the lymphatic vascular system, which is required for the trafficking of immune cells [46][47][48][49][50]. Tissue clearing can be combined with topological data analysis to extract geometric features without prior definition of geometric information, as shown in the recent analysis of blood and lymphatic vessels of cleared tissue [48].…”
Section: Tubulementioning
confidence: 99%